Reactive oxygen species in periodontitis - Dahiya, Parveen (Medknow Publications & Media Pvt Ltd, 2013)
Recent epidemiological studies reveal that more than two-third of the world's population suffers from one of the chronic forms of periodontal disease. The primary etiological agent of this inflammatory disease is a polymicrobial complex, predominantly Gram negative anaerobic or facultative bacteria within the sub-gingival biofilm. These bacterial species initiate the production of various cytokines such as interleukin-8 and TNF-α, further causing an increase in number and activity of polymorphonucleocytes (PMN) along with these cytokines, PMNs also produce reactive oxygen species (ROS) superoxide via the respiratory burst mechanism as the part of the defence response to infection. ROS just like the interleukins have deleterious effects on tissue cells when produced in excess. To counter the harmful effects of ROS, human body has its own defence mechanisms to eliminate them as soon as they are formed. The aim of this review is to focus on the role of different free radicals, ROS, and antioxidants in the pathophysiology of periodontal tissue destruction.